An Alcohol Abuse Early Intervention Approach with Mi’kmaq Adolescents - Mushquash, Christopher J.; Comeau, M. Nancy; Stewart, Sherry H. (First Peoples Child & Family Review, 2007)
This paper describes the development of and pilot results for an alcohol abuse early intervention program targeting at-risk Mi’kmaq youth conducted in partnership with the communities in which these youth live and the schools which they attend. This intervention was based on a previously-established, successful psychoeducational and cognitive-behavioral approach for at-risk adolescent drinkers from the majority culture that focuses on differentpersonality pathways to alcohol abuse in youth (Conrod, Stewart, Comeau, & MacLean, 2006). Through partnership and collaboration with two Mi’kmaq communities, the original intervention was adapted to be culturally appropriate for Mi’kmaq youth. The culturally-adapted intervention included traditional Mi’kmaq knowledge and teachings in order to make the program as meaningful and relevant as possible in the partner communities (Comeau et al., 2005). The pilot results were encouraging. Compared to pre-intervention, students who participated in the intervention drank less, engaged in less binge-drinking episodes (i.e., 5 drinks or more/occasion), had fewer alcoholrelated problems, and were more likely to abstain from alcohol use. Moreover, students who participated in the intervention also reduced their marijuana use at four-month post-intervention, even though the intervention was speciﬁcally designed to target alcohol misuse. No such signiﬁcant changes were observed in a non-random control group of eligible students who did not participate in the intervention. Future research should determine if this intervention is effective for at-risk youth in other First Nations communities across Canada, and whether the promising, but preliminary results with marijuana mean that the beneﬁts of the intervention might extend to adolescents’ use of substances other than alcohol.